Analisis Positioning Produk Shimmy Berdasarkan Persepsi Konsumen di Industri Camilan Kekinian - Risski Aufa Waradana; Nibita Floren; Irfan Assaukani Audadi; Ahmad Juan Shobari; Stephanny Lianardo (Jurnal Riset Multidisiplin Edukasi, 2025)
Amidst the growing dynamism of Indonesia’s modern snack industry, brands are challenged not only to satisfy consumer taste but also to align with shifting lifestyles and visual culture. Shimmy an emerging tuna-based snack brandpositions itself as a modern alternative to traditional street snacks, targeting urban youth who value uniqueness, trendiness, and nutrition. This study analyzes consumer perceptions of Shimmy, a tuna-based snack brand, compared to Yumchi and Chisum in Indonesia’s modern snack industry. Using a descriptive-quantitative approach with discriminant analysis, data were collected from 45 respondents aged 17–25 through product testing and questionnaires assessing ten perceptual dimensions. Results indicate that Shimmy excels in visual appeal, trend relevance, and brand uniqueness, while Yumchi ranks higher in daily usability and perceived suitability. Chisum shows low resonance across all dimensions. These findings highlight the importance of visual identity, lifestyle alignment, and differentiation in building strong brand positioning